Ileosigmoid Knotting in Pregnancy: A case Report Seen in Uganda. - Mutiibwa, D.; Tumusiime, G. (East and Central African Journal of Surgery, 2013)
Ileo-sigmoid knotting (ISK) refers to the intertwining of the ileum and the sigmoid colon. The incidence of ISK is not known but generally occurs in areas with high incidence of sigmoid volvulus such as Africa, Asia, Middle East, and South America. ISK is more common in adult males, particularly the old. ISK in pregnancy is not common but if it occurs, early surgical intervention is necessary to avert its associated morbidity and mortality. Normal pregnancy complaints may cloud the clinical picture of ISK and efforts to avoid radiological investigations may contribute to diagnostic delay. We report a case of a pregnant mother in her second trimester who was admitted at Mbarara Regional Referral Hospital with features of intestinal obstruction and exploratory laparotomy revealed ISK with gangrenous bowel. After surgery, she recovered very well, carried her pregnancy to term and delivered normally.
Keywords: Ileo-sigmoid knotting (ISK); Pregnancy; Uganda